Analisis Hubungan Higiene Perorangan dengan Kejadian Kecacingan Siswa Siswi SDN Barombong Kota Makassar - Kahar, Fitriani (UNM Environmental Journals, 2018)
This study aims to find out (1) hand washing related to the worm incidence of Makassar elementary school students, (2) nail hygiene associated with the incidence of helminthiasis in Makassar city elementary school students, (3) the use of footwear related to the incidence of helminthiasis in Makassar elementary school students , (4) the factors most associated with the incidence of helminthiasis in students of the elementary school in Makassar. The method used was analytic observational and laboratory with cross sectional design. The location of the study was carried out at Barombong Elementary School in Makassar City. The analysis used was Chi square then continued with logistic regression. The results of this study indicate that (1) hand washing is related to the incidence of helminthiasis in students of the Barombong Elementary School in Makassar City with a value (p = 0.011), (2) Nail hygiene associated with the incidence of helminthiasis in Makassar Barombong Elementary School students with a value (p = 0.021), (3) The use of footwear is not related to the incidence of helminthiasis in students of Barombong Elementary School in Makassar City with a value (p = 0.362), (4) hand washing is the variable most associated with Exp value (B) = 8.554. This study suggests the need for counseling and providing information to students about the need for individual hygiene, and the dangers of worm disease to prevent worm disease.